A Change Management Model and Its Application in Software Development Projects - Efe, Pınar; Demirörs, Onur; Demirörs, Onur (Elsevier, 2019)
Change is inevitable in software projects and software engineers strive to find ways to manage changes. A complete task could be easily in a team's agenda sometime later due to change demands. Change demands are caused by failures and/or improvements and require additional effort which in most cases have not been planned upfront and affect project progress significantly. Earned Value Management (EVM) is a powerful performance management and feedback tool for project management. EVM depicts the project progress in terms of scope, cost, and schedule and provides future predictions based on trends and patterns of the past. Even though EVM works quite well and widely used in disciplines like construction and mining, it is not the case for software discipline. Software projects require special attention and adoption for change. In this study, we present a model to measure change and subsequent rework and evolution costs to monitor software projects accurately. We have performed five case studies in five different companies to explore the usability of the proposed model. This paper depicts the proposed model and discusses the results of the case studies.
Keywords: Earned Value Management; Software project management; Performance measurement; Reworking; Change management